Role of Water Research Institutions in Nepal and its Impact on Policy Changes - Pradhan, Prachanda (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Not Available. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 17, July 2015